Active Component of Danshen (Salvia miltiorrhiza Bunge), Tanshinone I, Attenuates Lung Tumorigenesis via Inhibitions of VEGF, Cyclin A, and Cyclin B Expressions. (9th April 2013) - Tung, Yu-Tang; Chen, Hsiao-Ling; Lee, Cheng-Yu; Chou, Yu-Ching; Lee, Po-Ying; Tsai, Hsin-Chung; Lin, Yi-Ling; Chen, Chuan-Mu
Abstract : Tanshinone I (T1) and tanshinone II (T2) are the major diterpenes isolated from Danshen ( Salvia miltiorrhiza Bunge). Three human lung adenocarcinoma cell lines, A549, CL1-0, and CL1-5, were treated with T1 and T2 for the in vitro antitumor test. Results showed that T1 was more effective than T2 in inhibiting the growth of lung cancer cells via suppressing the expression of VEGF, Cyclin A, and Cyclin B proteins in a dose-dependent manner. Moreover, a transgenic mice model of the human vascular endothelial growth factor-A165 (h V E G F - A 165 ) gene-induced pulmonary tumor was further treated with T1 for the in vivo lung cancer therapy test. T1 significantly attenuated hVEGF-A165 overexpression to normal levels of the transgenic mice (Tg) that were pretreated with human monocytic leukemia THP-1 cell-derived conditioned medium (CM). It also suppressed the formation of lung adenocarcinoma tumors (16.7%) compared with two placebo groups (50% for Tg/Placebo and 83.3% for Tg/CM/Placebo; P < 0.01 ). This antitumor effect is likely to slow the progression of cells through the S and G2/M phases of the cell cycle. Blocking of the tumor-activated cell cycle pathway may be a critical mechanism for the observed antitumorigenic effects of T1 treatment on vasculogenesis and angiogenesis.